Inna teoria - Krajewska, Anna (Przestrzenie Teorii, 2019)
The article contains reflections on “a different theory of literature”. By emphasising the impossibility of maintaining a vision of theory as a history of courses, research methods, academic disciplines and other ‘isms’ and ‘turns’, the author suggests replacing this with ‘a different theory’. This is ‘different’ in that it is written as dramatography; different because it does not comprise uniform subject matter, but various interwoven discourses; different because it consolidates individual experiences and frequently develops away from one concept. This issue of “Przestrzenie Teorii” deals with theory emerging from art, theory rooted in and rooting itself in art.